Tumor-associated carbohydrates and immunomodulatory lectins as targets for cancer immunotherapy - Rodrigues Mantuano, Natalia (J Immunother Cancer, 2020)
During oncogenesis, tumor cells present specific carbohydrate chains that are new targets for cancer immunotherapy. Whereas these tumor-associated carbohydrates (TACA) can be targeted with antibodies and vaccination approaches, TACA including sialic acid-containing glycans are able to inhibit anticancer immune responses by engagement of immune receptors on leukocytes. A family of immune-modulating receptors are sialic acid-binding Siglec receptors that have been recently described to inhibit antitumor activity mediated by myeloid cells, natural killer cells and T cells. Other TACA-binding receptors including selectins have been linked to cancer progression. Recent studies have shown that glycan-lectin interactions can be targeted to improve cancer immunotherapy. For example, interactions between the immune checkpoint T cell immunoglobulin and mucin-domain containing-3 and the lectin galectin-9 are targeted in clinical trials. In addition, an antibody against the lectin Siglec-15 is being tested in an early clinical trial. In this review, we summarize the previous and current efforts to target TACA and to inhibit inhibitory immune receptors binding to TACA including the Siglec-sialoglycan axis.